Co-Encapsulation of Simvastatin and Doxorubicin into pH-Sensitive Liposomes Enhances Antitumoral Activity in Breast Cancer Cell Lines - Jaqueline Aparecida Duarte; Eliza Rocha Gomes; André Luis Branco De Barros; Elaine Amaral Leite (MDPI AG, 2023)
Doxorubicin (DOX) is a potent chemotherapeutic drug used as the first line in breast cancer treatment; however, cardiotoxicity is the main drawback of the therapy. Preclinical studies evidenced that the association of simvastatin (SIM) with DOX leads to a better prognosis with reduced side effects and deaths. In this work, a novel pH-sensitive liposomal formulation capable of co-encapsulating DOX and SIM at different molar ratios was investigated for its potential in breast tumor treatment. Studies on physicochemical characterization of the liposomal formulations were carried out. The cytotoxic effects of DOX, SIM, and their combinations at different molar ratios (1:1; 1:2 and 2:1), free or co-encapsulated into pH-sensitive liposomes, were evaluated against three human breast cancer cell lines (MDA-MB-231, MCF-7, and SK-BR-3). Experimental protocols included cell viability, combination index, nuclear morphological changes, and migration capacity. The formulations showed a mean diameter of less than 200 nm, with a polydispersity index lower than 0.3. The encapsulation content was ~100% and ~70% for DOX and SIM, respectively. A more pronounced inhibitory effect on breast cancer cell lines was observed at a DOX:SIM molar ratio of 2:1 in both free and encapsulated drugs. Furthermore, the 2:1 ratio showed synergistic combination rates for all concentrations of cell inhibition analyzed (50, 75, and 90%). The results demonstrated the promising potential of the co-encapsulated liposome for breast tumor treatment.